Analysis of Factors Affecting the use of Accounting Information Systems in Micro, Small, and Medium Enterprises (MSMEs) Culinary in Medan City - Laia, Insaf; gaol, Perawati Lumban; Br Sinuhaji, Eginta Kaduna; Saraswati, Dwi (Indonesian Journal Publisher, 2024)
Culinary Micro, Small and Medium Enterprises (MSMEs) are an important sector in the Indonesian economy. In Medan, this sector has developed significantly, encouraging many entrepreneurs to set up culinary businesses. However, many of them still have difficulty managing their finances effectively. This can hinder the growth and development of their business. The implementation of an Accounting Information System (AIS) can help culinary MSMEs manage their finances effectively. This research aims to analyze the influence of educational factors, business experience and business scale on the implementation of AIS in culinary MSMEs in Medan. The research method used is analysisliterature. The research results show that the factors of education, business experience, and business scale have a positive influence on the implementation of AIS in culinary MSMEs in Medan.